(untitled) (Baghdad Science Journal, 2016)
This work was influenced the separation and preconcentration steps were carried out to determination of metformin (MET) in pharmaceutical preparations and human serum samples. Complex formation method and cloud-point extraction (CPE) coupling with UV-Visible spectrophotometry were used to investigated of study target.The results has showed the best optical characteristic for calibration curve and statistical data which were obtained under optimum conditions. The first method is based on the reaction of MET with nickel (II) in alkaline medium an absorption maximum ?)max) at 434nm. ’’Beer’s low’’ is obeyed in the concentration range (10-100µg.ml-1) with molar absorptivity of 3.9x103 L.mol-1.cm-1.The limit of detection and quantitation values were 2.37 and7.11 µg.ml-1 respectively. The second method based on extraction of traces amounts of MET using the cloud-point extraction (CPE). This method implicated for using of a nonionic surfactant (Triton x-114) as an extraction medium which was entrap the hydrophobic complex formed between MET and nickel(ii) in basic medium as reaction system for designing the CPE procedure. The optimum conditions were similar the first method expect the amount of surfactant which was 0.5 ml. The concentrations range of calibration curve from 3.5to100 µg.ml-1 and molar absorptivity of 1.2x104 L.mol-1.cm-1. In this method was access to less of concentrations in Limit of detection and quantitation which were 0.74and 2.22 µg.ml-1 respectively. The precise (RSD %) and accuracy (recovery %) of both methods were ranged between 0.24-0.47, 97.86-98.68 respectively. The data of two methods were appeared high acceptable with standered of British Pharmacopoeia through using statistic methods (f-test and t-test), that they may be used in analysis of MET.